2001
DOI: 10.2134/jeq2001.303903x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cadmium on Biosolids‐Amended Soils

Abstract: Debate exists over the biosolid phase (organic or inorganic) responsible for the reduction in phytoavailable Cd in soils amended with biosolids as compared with soils amended with inorganic salts. To test the importance of these two phases, adsorption isotherms were developed for soil samples (nine biosolids-amended soils and their five companion controls) and two biosolids samples from five experimental sites with documented histories of biosolids application. Subsamples were treated with 0.7 M NaClO to remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 43 publications
12
64
1
1
Order By: Relevance
“…easily reducible Fe and Mn) in Pb sorption is greater in the manure compared to the biosolids. This result is in agreement with the observations of Li et al (2001), Hettiarachchi et al (2003), Lombi et al (2002), and Scheckel and Ryan (2004) that showed the significant role of the inorganic fractions of organic amendments in Pb sorption. Additionally, a 0.8 unit decrease in pH of the manure after removing easily reducible Fe and Mn could explain reduction (28.1%) of Pb sorption of this amendment.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…easily reducible Fe and Mn) in Pb sorption is greater in the manure compared to the biosolids. This result is in agreement with the observations of Li et al (2001), Hettiarachchi et al (2003), Lombi et al (2002), and Scheckel and Ryan (2004) that showed the significant role of the inorganic fractions of organic amendments in Pb sorption. Additionally, a 0.8 unit decrease in pH of the manure after removing easily reducible Fe and Mn could explain reduction (28.1%) of Pb sorption of this amendment.…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with the finding of Li et al (2001) that indicated removal of OC reduced sorption of Cd for biosolids-amended soil samples. However, in that research the increased Cd sorption attributed to biosolids application was still present compared to the control soil that indicates the role of the inorganic fraction of the biosolids.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations